Food MSMEs Business Communication Strategy in Establishing Cooperation with Local Distribution Partners - Fariska Maulidah Hikmawati (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
This study aims to analyze the business communication strategies employed by food MSMEs in Bekasi in establishing partnerships with local distribution partners. The research is grounded on the premise that communication is a fundamental aspect of building sustainable business relationships, particularly for MSMEs that often operate with limited resources. A qualitative approach with a case study method was applied to explore in depth the communication patterns between MSMEs and their distribution partners. Data collection techniques included in-depth interviews, observations, and documentation. The data were analyzed thematically using the interactive model of Miles, Huberman, and Saldana. The findings reveal that trust-based interpersonal communication serves as the primary strategy used by MSMEs to build distribution cooperation. Communication is conducted directly and through digital media such as WhatsApp and social media, but remains largely informal and lacks systematic documentation. Despite this, the strategy is considered effective in fostering strong partner relationships. Challenges identified include limited production capacity, high expectations from distribution partners, and a lack of formal communication literacy. The study concludes that communication support and training are essential to help MSMEs develop more professional and sustainable communication strategies.